Applications of Interior Space Design According to Shape Generation Systems: عبد الكريم علي حسين (Al-Academy, 2019)
Treatises concerning analyzing the interior spaces multiplied and their directions varied, that some of them analyzed the interior space on the basis of the intellectual and philosophical affiliation or the historical period and others in the light of the concept and mechanisms of the shape. The researcher has not been able to find a research that dealt with analyzing the space within the systems of shape generation, thus it is possible to determine the research problem with the following question: to what extent is it possible to analyze the interior space based on systems of shape generation? As far as the importance of the research is concerned, it sheds light on five of the systems of the shape generation which are: Syntax, shape grammar, Lindenmayer system, automated cellular, Genetic algorithms) and the study of the similarities and differences between them in addition to the importance of the research in providing a mechanism for analyzing the interior spaces in order to reach a space quality measure in the formal and expressive sides. The research aim is to apply the systems of the shape generation in analyzing the interior space. The results of the study included: coming up with a form for the analysis that includes the acting and structural sides to analyze the interior spaces. Repeating the use of the shape generation systems for any interior space will provide a visual variability and visual multiplicity. The generation system (shape grammar) is considered the most widely used in the interior spaces. The concept of acting of the interior design is a mixture between the analytic and structural readings for the work, that they are inseparable